Analysis of Particular Parameters of a Social Situation of the Development of a Pre-School Aged Child in Conditions of the Family and Pre-School Education Institutions - Lehankova, Volha; Sotsenko, Tatyana; Chikileva, Darja (Զանգակ հրատ.)
The changing conditions of social development give considerable relevance to a study of parameters of a social situation of the development of the individual at the stage of childhood. The aim of the study: research of characteristics of a social situation of the development of a pre-school aged child at the present stage of society. The study was conducted in the cities of Minsk and Zhlobin (The Republic of Belarus); children of pre-school education institutions (n=100) and their parents (n=28) participated in the study. Diagnostic tools: “Parents composition”, “Choice in action”, “Stair”, “Finish a story”, a conversation on three clusters of unfinished sentences. The results of the empirical study revealed a predominance of non-constructive child-parent interaction in the respondents’ families. The analysis of a child’s position in a group of an education institution generally revealed the existence of a favourable climate in the given subsystem of relations. Preferences in one or another type of interactions are connected with the self-assessment, a position in a group and a level of awareness of ethical norms and values. Optimization of the main parameters of pre-school aged children interaction is a relevant direction of the support of positive socialization.
Keywords: Pedagogy